Extensins: Self-Assembly, Crosslinking, and the Role of Peroxidases - Mishler-Elmore, John W.; Zhou, Yadi; Sukul, Abhijit; Oblak, Mercedes; Tan, Li; Faik, Ahmed; Held, Michael A. (Frontiers in Plant Science, 2021)
The extensin network is elaborated by the covalent intermolecular crosslinking of extensin glycoprotein monomers and its proper assembly is important for numerous aspects of basic wall architecture and cellular defense. In this review, we discuss new advances in the secretion of extensin monomers and the molecular drivers of extensin network self-assembly. Many of the functions of extensins are conferred through covalent crosslinking into the wall, so we also discuss the different types of known intermolecular crosslinks, the enzymes that are involved, as well as the potential for additional crosslinks that are yet to be identified. Extensins also function in wall architecture independent of crosslinking status and therefore we explore the role for non-crosslinking extensins. As extensin crosslinking is upregulated in response to wounding and pathogen infection, we discuss a potential regulatory mechanism to control covalent crosslinking and its relationship to the subcellular localization of the crosslinking enzymes.